2018
DOI: 10.1253/circj.cj-17-1295
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Fatty Acid-Binding Protein 4 Concentration Predicts the Progression of Carotid Atherosclerosis in a General Population Without Medication

Abstract: Background: Fatty acid-binding protein 4 (FABP4), which is expressed in both adipocytes and macrophages, is secreted from the cells and acts as an adipokine. An elevated circulating FABP4 level is associated with insulin resistance and atherosclerosis. Methods and Results:We investigated the causative association between FABP4 level and progression of atherosclerosis in subjects of the Tanno-Sobetsu Study, a population-based cohort. In 281 subjects without medication (male/female: 109/172) in the year 2010 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…In ApoE-deficient mice and in the human microvascular endothelium, previous work shows that A-FABP has an independent role in atherogenesis; additionally, enhanced expression of A-FABP was associated with reduced expression of eNOS and nitric oxide (NO) production [19,23]. Additional work showed an association between serum A-FABP levels and endothelial dysfunction [24,25,26]. Furuhashi et al reported that serum levels of A-FABP correlated positively with changes in carotid intima-media thickness in subjects without medications [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ApoE-deficient mice and in the human microvascular endothelium, previous work shows that A-FABP has an independent role in atherogenesis; additionally, enhanced expression of A-FABP was associated with reduced expression of eNOS and nitric oxide (NO) production [19,23]. Additional work showed an association between serum A-FABP levels and endothelial dysfunction [24,25,26]. Furuhashi et al reported that serum levels of A-FABP correlated positively with changes in carotid intima-media thickness in subjects without medications [25].…”
Section: Discussionmentioning
confidence: 99%
“…Additional work showed an association between serum A-FABP levels and endothelial dysfunction [24,25,26]. Furuhashi et al reported that serum levels of A-FABP correlated positively with changes in carotid intima-media thickness in subjects without medications [25]. Aragones et al demonstrated that circulating A-FABP levels were associated with endothelial dysfunction as measured by reactive hyperemia index in DM patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating FABP4 is independently associated with the level of PCSK9, which binds to and degrades the low-density lipoprotein (LDL) receptor, suggesting associations with hypercholesterolemia and cardiovascular risk 95) . Furthermore, the basal FABP4 level is independently associated with change in carotid intima-media thickness, a marker of atherosclerosis, per year, indicating that FABP4 level predicts progress of atherosclerosis 96) . It has also been reported that serum FABP4 level predicts long-term cardiovascular events and mortality 82, 9799) .…”
Section: Circulating Fabp4 Levelmentioning
confidence: 99%
“…Lipolysis-associated secretion of FABP4 from adipocytes is caused by a non-classical secretion pathway (7,11) despite the lack of signal peptides (1), and secreted FABP4 has effects as an adipokine on insulin resistance, atherosclerosis and vascular remodeling (7,8,12). An elevation of FABP4 concentration is associated with metabolic disorders and cardiovascular events (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). It has recently been shown that FABP4 concentration is modulated by several therapeutic drugs for diabetes mellitus, dyslipidemia and hypertension (24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%